Irrigation and drainage performance assessment : practical guidelines - Bos, Marinus Gijsberthus, 1943- (CABI Pub., 2005)
"This book draws on over twenty years of experience gained in irrigation and drainage performance assessment. Performance assessment is an essential management task. If the use of water for irrigation is to be improved then we must understand current levels of performance and identify measures for improvement. This book provides guidelines to enable practitioners to apply the processes and procedures that have evolved. Developed by a working group of the International Commission on Irrigation and Drainage (ICID) it provides a generic framework for performance assessment with guidance on the theory and practice of how to audit and assess the performance of irrigation and drainage schemes. It will be of significant interest to those working within the areas of irrigation, drainage, soils and agricultural engineering."--Jacket